2022
DOI: 10.1186/s12891-022-05539-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three bone graft struts for interbody fusion using a posterior approach for lower lumbar spinal tuberculosis in adults: a midterm follow-up study

Abstract: Background This retrospective observational study was conducted to compare midterm outcomes of three bone graft struts for interbody fusion using a posterior approach in adults with lower lumbar spinal tuberculosis. Methods A total of 126 lower lumbar spinal tuberculosis patients were treated by one-stage posterior debridement, interbody fusion, and instrumentation. Forty-one patients (group A) were treated with autogenous bone graft for interbody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Meanwhile, we discovered that TM has a unique advantage in reducing postoperative Cobb angle loss when compared with AG and AM, probably attributing to a reduction of bone resorption [ 9 ]. This result is akin to previous clinical studies demonstrating that intervertebral titanium mesh bone graft performed better in maintaining lordosis and preventing collapse than autogenous bone graft [ 14 ]. Based on these results, TM is likely to have a promising future in correcting the deformity and maintaining spinal stability.…”
Section: Discussionsupporting
confidence: 77%
“…Meanwhile, we discovered that TM has a unique advantage in reducing postoperative Cobb angle loss when compared with AG and AM, probably attributing to a reduction of bone resorption [ 9 ]. This result is akin to previous clinical studies demonstrating that intervertebral titanium mesh bone graft performed better in maintaining lordosis and preventing collapse than autogenous bone graft [ 14 ]. Based on these results, TM is likely to have a promising future in correcting the deformity and maintaining spinal stability.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies of posterior-only approach in treating singlelevel tuberculosis had reported the average bleeding to be over 500 mL [ 26 - 29 ], consistent with our result in posterior approach. In contrast, the median blood loss in SP-OLIF group was significantly reduced (320 [450–290] mL vs. 500 [600–400] mL, p<0.05), which should be ascribed to the following aspects.…”
Section: Discussionsupporting
confidence: 91%
“…The primary causative agent, Mycobacterium tuberculosis, typically leads to an infection in the spine and large joints due to their abundant blood supply. The spine is the most frequently affected skeletal site, representing the majority of skeletal TB cases [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%